Potential fitness consequences of roosting spatiotemporal selection in an endangered endemic damselfly: conservation implications - Mahdjoub, Hayat; Zebsa, Rabah; Amari, Hichem; Bensouilah, Soufyane; Zouaimia, Abdelheq; Youcefi, Abdeldjalil; Khelifa, Rassim (Frontiers in Ecology and Evolution, 2023)
Understanding habitat requirements of species of conservation concern is central for their conservation and the management of their habitat. Although much of the research attention has been focused on reproductive sites, the understanding of roosting behavior and microhabitat selection, and their potential fitness consequences is also crucial. Here, we assess the roosting behavior of an endangered endemic damselfly Calopteryx exul Selys in a lotic habitat of Northeast Algeria. Based on marked individuals, we specifically investigated their vertical and horizontal distribution at roosting sites, as well as the timing of roosting and its correlation with lifespan (as a measure of fitness). We found that individuals were philopatric to roosting sites and less so to vertical stratification. Roosting sites were used for both foraging and roosting.Individuals that occupied lower strata in roosting sites had longer lifespans and ceased roosting earlier. Average temperature of the day affected the timing of roosting such that on warm days roosting started later and ended earlier. Individuals with longer lifespans roosted earlier, suggesting potential scramble competition for roosting sites. Our results suggest that C. exul individuals show variability in the vertical and horizontal location as well as the timing of roosting, and these choices potentially have fitness consequences. This study highlights the importance of bank vegetation as roosting sites for lotic insects, and emphasizes the benefits of protecting these sites and including them as integral parts of the conservation plans of species.